2006
DOI: 10.1152/ajpgi.00472.2005
|View full text |Cite
|
Sign up to set email alerts
|

PI3-kinase activity modulates apo B available for hepatic VLDL production inapobec-1−/−mice

Abstract: Insulin regulates hepatic VLDL production by activation of phosphatidylinositide 3-kinase (PI3-kinase) which decreases apo B available for lipid assembly. The current study evaluated the dependence of the VLDL apolipoprotein B (apo B) pathway on PI3-kinase activity in vivo. VLDL production was examined in B100 only, apo B mRNA editing catalytic subunit 1 (apobec-1 Ϫ/Ϫ ) mice, using the Triton WR 1339 method. Glucose injection suppressed VLDL triglyceride production by 28% in male and by 32% in female mice comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 37 publications
(49 reference statements)
1
36
0
1
Order By: Relevance
“…The interface between PI3K-dependent signaling and apoB assembly and secretion is not known in detail, although in some studies, insulin-mediated signaling, via PI3K and Akt, regulates MTP expression and, hence, VLDL particle number and size (18,29,31,32). Although MTP is the target for some forms of PI3K-mediated regulation of VLDL assembly (32), MTP expression was unaffected by ABCA1 deficiency in this study (Fig.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The interface between PI3K-dependent signaling and apoB assembly and secretion is not known in detail, although in some studies, insulin-mediated signaling, via PI3K and Akt, regulates MTP expression and, hence, VLDL particle number and size (18,29,31,32). Although MTP is the target for some forms of PI3K-mediated regulation of VLDL assembly (32), MTP expression was unaffected by ABCA1 deficiency in this study (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…To study the effect of in vivo inhibition of PI3K on VLDL TG and apoB production, mice were injected with the PI3K inhibitor wortmannin (1.5 g/g body weight) 1 h prior to detergent injection as described previously (18). Fifty l of blood were collected from anesthetized mice by retro-orbital bleeding at 0, 1, 2, and 4 h after injection.…”
Section: Animals and Diet-generationmentioning
confidence: 99%
“…kinase pathways ( 30,31,46,47 ). Insulin stimulation appears to specifi cally inhibit the second step of VLDL assembly such that insulin resistance results in increased hepatic production of VLDL1 ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In rat hepatocytes, insulin was shown to inhibit the maturation phase of VLDL assembly by preventing lipid transfer to pre-VLDL particles, resulting in preferential degradation of apoB-100 from these pre-VLDL particles (26). Furthermore, Chirieac et al (27) examined apoB-100 secretion by pulse-chase in primary mouse hepatocytes and concluded that blocking the effect of insulin with wortmannin increased the amount of apoB-100 available for secretion. It was not possible to distinguish decreased synthesis from increased cotranslational degradation.…”
Section: Discussionmentioning
confidence: 99%